THE REASON BEHIND THE END OF THE OPERATION MARE NOSTRUM (OMN): A Successful Search and Rescue Operation by Italian Navy during 2013-2014 - Aan Fitri Murniati (HI 16 UMY 041, 2016)
*41 The European Union (EU) has been facing the biggest humanity crisis since 2013. It sounds to have a serious problem on dealing with the coming migrant/immigrant people from many conflicting area in the world such as Syria (from the civil war), North Africa (especially from Eritrea which is rooted in its harsh military services), Iraq, Libya, Afghanistan and many more. Operation Mare Nostrum (OMN) was established last October, 2013 and was considered as the most successful program with Italy as the sole host-state which was also held by their navy. It aimed to tackle the dramatic increase of migratory flows during the second half of the year and consequent tragic ship wreckages off the island of Lampedusa. In the last quarter of 2013, EU rejected to continue this operation and being criticized by many parties. The EU’s prediction and Italy’s decision were blamed as a wrong decision. However, there would be always reason behind the decision which was made by the Italy to end the OMN. Keyword: Operation Mare Nostrum, Migrant Crisis, Italian Navy, Joint Responsibility, Decision Making